Borders as spaces of concurrent territorial configurations. The case of the Republic of Mali in Africa (Huellas, 2018)
When we discuss borders in Africa, we enter a vague and complex field. Any theoretical or conceptual approach to the subject might lead us to remove from the analysis other theoretical perspectives and concrete realities which are developed slyly in border spaces. When the role of the State and the effect of its politics are underestimated, we run the risk of falling into “essentialist brotherhood”, minimizing existing conflicts and thus making it difficult to visualize the asymmetries and the dimensions of inclusion and exclusion (Grimson, 2011).On the other hand, borders are built through processes of relational hegemony, where, even though certain logics of power are imposed, spaces of resistance also come into play. Tobío (2014) considers the concept of territoriality as instance of dominance and also as instance of subordination. Both territorialities allow us to understand the process of construction of borders and of their dynamics.We will focus our analysis on the case of the Republic of Mali and the different borders that nowadays are being developed in the area: the border of foreign business organizations, the borders of the controlled city, the borders of the Tuareg people, the borders of the configuration imposed by the Afro-Islamic community, and the borders that mark the physical and environmental presence of the Sahelian region. Our aim is to identify the territorial configurations presented by the borders along with the underlying strategies and territorial anchoring displayed by the different actors in their territory, basing our analysis on the spatial categories mentioned above.
Keywords: border; territoriality; power; strategies